Variations of the maximum blood flow velocity in the carotid, brachial and femoral arteries in a passive postural changes by a Doppler ultrasound method - Noor Azmi, Azran Azhim; Hirao, Yuji; Kinouchi, Yohsuke; Yamaguchi, Hisao; Yoshizaki, Kazuo (IEEE, 2004)
We have developed a blood flow velocimeter to measure maximum blood flow velocity (MBFV) in carotid, brachial and femoral arteries simultaneously by using a Doppler ultrasound technique. This measurement system is based on a continuous wave Doppler ultrasound method with two semicircular piezoelectric (PZT) transducers, one continuously transmitting ultrasound, and the other continuously receiving the echoes. This report is to investigate variations of MBFV in 3 arteries of 5 healthy normal male volunteers during passive postural changes in supine, 90 degrees head-down-tilt (HDT) and 90 degrees head-up-tilt (HUT) respectively. As a result of these measurements, we could confirm that MBFV in those arteries especially in brachial and femoral are increased by supine to HDT posture and are decreased by supine to HUT posture. But, it's just changed a little in carotid artery. An increasing and a decreasing in MBFV are expected to be an effect of venous pressure and a constant MBFV in carotid artery is caused a cerebral autoregulation.